Interpretation of Family Relations in the Content of Values - Axmedova, Maqsuda (Центр Научных Публикаций (buxdu.uz), 2023)
The family is the basis and core of any society. Human qualities such as honesty, honor, kindness, loyalty, hard work, and patriotism, which are the ancient values and traditions of our people, are formed first of all in the family. In particular, the strength, stability, and longevity of Uzbek families is due to their reliance on these spiritual traditions. Taking this into account, "researching the spiritual foundations of Uzbek families" is important